Effectiveness of E-Catalog in Procurement at Bandar Lampung Library and Archives Service - Anggalia Wibasuri; Antonius Ginting; Elvirayhan Asrul; Yuliyana Yuliyana (Reviu Akuntansi, Manajemen, dan Bisnis, 2025)
Purpose: This study evaluated the effectiveness of E-Catalogs in increasing efficiency, transparency, and accountability, and identifying implementation barriers to formulate more appropriate policy recommendations. Methodology: This study used a descriptive qualitative approach. Data collection techniques included interviewing sources, direct observation that directs the procurement of goods and services, and collecting various documents related to the research topic. Results: This study aimed to analyze the effectiveness of the implementation of an Electronic Catalog (E-Catalog) in the government procurement process for goods/services at the library and archives service level in Bandar Lampung City. Conclusions: The results of this study show that the E-Catalog is an effective procurement instrument for improving the performance of government procurement of goods and services, especially in terms of efficiency, transparency, and accountability within the Library and Archives Service of Bandar Lampung City. Limitations: This study aims to evaluate the effectiveness of the implementation of E-Catalog in the procurement of goods and services at the Library and Archives Service of Bandar Lampung City, particularly in increasing efficiency, transparency, accountability, supervisory functions, and identifying implementation obstacles to formulate more appropriate policy recommendations. Contributions: This study uses Presidential Regulation No. 16 of 2018 and interviews with procurement officials at the Library and Archives Service.